ДИСЦИПЛІНА «ДІЛОВА АНГЛІЙСЬКА МОВА» В СУЧАСНИХ СОЦІАЛЬНО-ЕКОНОМІЧНИХ УМОВАХ (Педагогіка вищої та середньої школи, 2008)
In the article the basic forming aspects of professional communicative competence and teaching methods of business English by improvement of teaching projects’ quality are considered. One of the basic principle o f the proposed methodic is autonomy of creative educational process.